Aktivitas Inhibitor α-Glukosidase Ekstrak Etanol Daun Kenitu (Chrysophyllum cainito L.) (α-Glucosidase Inhibitor Activity of Ethanol Extract Kenitu Leaves (Chrysophyllum cainito L.)) - Fatimatuz Zuhro; Endah Puspitasari; Siti Muslichah; Moch. Amrun Hidayat (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Kenitu (Chrysophyllum cainito L.) grows in Jember region, East Java, with several variants which can be distinguished from the color and shape of the fruit. They are small round (BK), large round (BB), green oval (HL), and red round (MB). Kenitu leaves have been shown to provide antidiabetic activity in vivo, but the molecular mechanism still unknown yet. One of the oral antidiabetic is a class of α-glucosidase inhibitor. This research aimed to test the activity of Saccharomyces cerevisiae α-glucosidase inhibitor of several variants of kenitu leaves in Jember, as well as phytochemical screening. Simplicia powder was extracted using 70% ethanol with ultrasonication method to obtain a thick extract. α-glucosidase inhibitor activity test was carried out on the negative control solution (without extract) and the sample solution (extract) using chromogenic method. Phytochemical screening was done by TLC and tube test. IC50 value of ethanol extract kenitu leaves variant BK, BB, HL, and MB were 5.476 ± 0.039, 4.869 ± 0.018, 9.465 ± 0.012, and 11.836 ± 0.048 µg/ml, respectively. Based on the LSD test, IC50 values between variants of kenitu leaves were significantly different (p < 0,05). Phytochemical screening result showed that ethanol extract kenitu leaves contain saponin, triterpenoids, flavonoids, and phenolic compounds. Those compounds were suspected to contribute on α-glucosidase inhibitor activity, but more study still needed to isolate the active compounds and evaluate each isolate for its α-glucosidase inhibitor activity. Keywords: α-glucosidase inhibitor, kenitu leaves, ethanol extract